Diagnostic Dilemma in the Treatment of a Fatal Case of Bloody Diarrhea - Sidharth Mahapatra MD, PhD; Sara A. Michie MD; Karl Sylvester MD; David Cornfield MD (SAGE Publishing, 2016)
Although diarrhea is the most commonly reported pediatric illness in the United States, mortality is usually a rare and unexpected event. We report the case of a healthy 13-month-old male that succumbed to a diarrheal illness of unclear etiology. Presenting signs included frequent nonbloody stools that progressed to frankly bloody stools over 72 hours. Associated symptoms included fever, tenesmus, relief with stool passage, and significant fatigue. On examination, the patient appeared tired and lay with legs curled toward his chest. The abdominal exam was remarkable for hypoactive bowel sounds, diffuse tenderness to palpation without guarding or rebound pain, and intermittent prolapse of rectal tissue. Abdominal plain films demonstrated a paucity of bowel gas, especially in the rectum; and ultrasound revealed thickening of bowel loops in the left lower quadrant. Abdominal computed tomography scan showed decreased enhancement of the mucosa of the rectosigmoid colon. The patient deteriorated rapidly with cardiorespiratory arrest occurring 48 hours after admission. Despite a protracted effort at cardiopulmonary resuscitation, perfusing heart rate or rhythm could not be reestablished. Autopsy revealed infarction and necrosis of the rectosigmoid colon with invasive gram-negative bacilli. Here we present his perplexing case, diagnostic evaluations, and suggest a unifying diagnosis.